Study of Nonlinear Periodic Optical System - H. Alatas; A.A. Iskandar; M. O. Tjia; T.P. Valkering (Journal of Mathematical and Fundamental Sciences, 2002)
We give a brief review of some results of our study on one-dimensional shallow nonlinear Bragg grating with nonlinear modulation and deep nonlinear Bragg grating.